2014
DOI: 10.1186/1471-2253-14-125
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management of patients undergoing bariatric surgery: two year experience in a single institution in Switzerland

Abstract: BackgroundIn the field of anesthesia for bariatric surgery, a wide variety of recommendations exist, but a general consensus on the perioperative management of such patients is missing. We outline the perioperative experiences that we gained in the first two years after introducing a bariatric program.MethodsThe perioperative approach was established together with all relevant disciplines. Pertinent topics for the anesthesiologists were; successful airway management, indications for more invasive monitoring, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…In other words, this evaluation indicates how big the error is when the method predicts that the surgery will end in, for instance, 25 minutes. A reliable RSD prediction of 25 minutes is particularly important as it is the time required for preparing the next patient for both cholecystectomy [4] and bypass surgeries [20]. The performance of RSDNet and the Naïve approach are compared since these approaches do not rely on manual annotations, enabling them to be more easily scaled up to different surgery types.…”
Section: Long Surgeriesmentioning
confidence: 99%
“…In other words, this evaluation indicates how big the error is when the method predicts that the surgery will end in, for instance, 25 minutes. A reliable RSD prediction of 25 minutes is particularly important as it is the time required for preparing the next patient for both cholecystectomy [4] and bypass surgeries [20]. The performance of RSDNet and the Naïve approach are compared since these approaches do not rely on manual annotations, enabling them to be more easily scaled up to different surgery types.…”
Section: Long Surgeriesmentioning
confidence: 99%
“…[9] However, advanced surgical skills are required to perform a TEP hernioplasty due to a different view of pelvic anatomy and a narrow dissection plan. [10,11] According to a comprehensive study, the mean operative time for a TEP procedure varied between 55 and 95 minutes, depending on surgical experience. [12] In a prospective study of 30 cases, Krishna et al [13] reported that the mean operative time was 62.13 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons with previous literature are constrained to a limited number of single-centred studies published in this area. These single institutional reports came primarily from established bariatric units and most of their patients were managed with well-defined or protocolised guidelines involving an advanced level of preoperative investigation and preoperative assessment [10][11][12] . Our study incorporated eight separate ICUs servicing every hospital in Western Australia and encompassing differing approaches to bariatric surgery, reflecting how anaesthesia was conducted for bariatric surgery in a 'real world' setting.…”
Section: Discussionmentioning
confidence: 99%
“…While intravenous cannulation in obese patients can be problematic, even in ideal conditions, delaying larger bore venous access until a clinical deterioration is evident, when it may be even more difficult, can delay resuscitation with potentially serious consequences. Based on this assumption, one institution has a prerequisite requirement for a certain minimum size of peripheral intravenous cannula, below which central venous access is recommended 10 . In the recently published "Peri-operative management of the obese surgical patient 2015" by the Association of Anaesthetists of Great Britain and Ireland Society for Obesity and Bariatric Anaesthesia, the minimum size of the intravenous cannula needed has not been specified, but they did recommend having two intravenous cannulae as "prudent" without a reference to support this statement.…”
Section: Discussionmentioning
confidence: 99%